Boron-nitrogen-carbon-based cobalt-nickel double-monatomic electrocatalyst as well as preparation method and application thereof
By preparing boron-nitrogen carbon-based cobalt-nickel double single-atom electrocatalyst, the H2/CO ratio is maintained in a wide voltage range by using the interaction between Co and Ni atoms, the synthesis gas ratio fluctuations and insufficient catalyst stability in the prior art are solved. The problem of this problem has achieved efficient and stable synthesis gas generation, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411417387.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to stably generate a synthesis gas of a specific H2/CO ratio within a wide voltage range, and the activity and stability of the catalyst are insufficient, which cannot meet the needs of industrial applications.
Using cobalt chloride and nickel chloride as metal sources, boric acid and urea as carbon sources, the boron nitrogen carbon-based cobalt nickel bismona electrocatalyst is prepared by high-temperature pyrolysis and acid etching to ensure the interaction between Co and Ni atoms. Keep the H2/CO ratio stable within the voltage range of -0.47~-0.87V vs.RHE, and controllable modulation of the H2/CO ratio is achieved by adjusting the precursor composition.
The stable generation of H2/CO ratios in a wide voltage range is achieved. The catalyst has excellent stability and high efficiency performance. It is suitable for industrial production. It can maintain good catalytic performance during the 20-hour electrolysis process and is significantly in the gas diffusion electrolytic cell. Increase current density.
Smart Images

Figure CN119221023A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of energy materials and electrochemistry, relates to an electrocatalytic CO2 reduction reaction, and specifically relates to a boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst and a preparation method and application thereof. Background Art
[0002] The production of syngas by CO2 electroreduction in aqueous solution is an important way to achieve sustainable development, and the key lies in the design and preparation of highly active and highly stable electrocatalysts. Metal dual-site catalysts (such as metal alloys, bimetallic oxides, bimetallic single atoms, etc.) have shown great potential in the preparation of co-reduction syngas because they can catalyze the reduction of reactants CO2 and H2O molecules respectively. However, the thermodynamic stability of CO2 molecules makes their activation and conversion more difficult, and the potential window for the preparation of syngas with a specific H2 / CO ratio is often narrow, which is not conducive to the stable generation of syngas driven by intermittent renewable energy such as wind power and photovoltaics. Therefore, the design and preparation of an electrocatalyst with high activity, high stability and stable generation of syngas H2 / CO ratio in a wide voltage range is a research focus in the field of electrocatalysis and a difficult problem that needs to be solved urgently.
[0003] At present, carbon-based metal double single-atom catalysts have shown broad application prospects in the catalytic conversion of CO2 to produce synthesis gas. X ) is the catalytic active site for CO2 reduction reaction and hydrogen evolution reaction. For example, document 1 (L. Wang, et al. J. Am. Chem. Soc. 145 (2023) 13462-13468.) uses NiPc, FePc, and NaCl as precursors, and obtains graphene-supported Ni-Fe double single-atom electrocatalysts after freeze-drying-pyrolysis-acid etching. By adjusting the loading amount of Ni and Fe atoms in the catalyst, the effective regulation of the H2 / CO ratio of the synthesis gas can be achieved. Although the catalyst can obtain a synthesis gas with an adjustable H2 / CO ratio, the synthesis gas ratio fluctuates greatly with the change of voltage, which cannot meet the practical industrial applications well.
[0004] In view of this, the present invention introduces a boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst with a simple preparation process and easy industrial production and a preparation method thereof, which is applied to the electroreduction of CO2 to produce synthesis gas and exhibits excellent catalytic performance. Among them, the Co single atom is the main active site for the production of H2, and the Ni single atom is the main active site for the production of CO. The interaction between Co and Ni atoms can achieve a wide voltage range of -0.47 to -0.87V vs. RHE, and the H2 / CO ratio of the synthesis gas is maintained at 1.5. In addition, by adjusting the Co and Ni loading in the catalyst, the H2 / CO ratio can be controlled and adjusted between 0.5 and 3. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst and its preparation method and application. The preparation process is simple and the prepared catalyst can achieve stable generation of synthesis gas with a specific H2 / CO ratio within a wide voltage range, while exhibiting excellent catalytic stability.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A method for preparing a boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst, using cobalt chloride and nickel chloride as metal sources, boric acid as a boron source, polyethylene glycol-2000 as a first carbon source, urea as a nitrogen source and a second carbon source, and adopting a simple high-temperature pyrolysis and acid etching method. The specific preparation steps are as follows:
[0008] (1) Weigh appropriate amounts of cobalt chloride, nickel chloride, boric acid, urea, and polyethylene glycol-2000 into a beaker, add deionized water, stir for 10 to 12 hours, and evaporate to dryness to obtain a catalyst precursor;
[0009] (2) placing the catalyst precursor obtained in step (1) in a tubular furnace, performing a first heat treatment in an inert atmosphere, etching in an acid solution, and performing a second heat treatment in an inert atmosphere to obtain a boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst.
[0010] Furthermore, in step (1), the mass ratio of cobalt chloride to nickel chloride is 1:5 to 5:1, preferably 1:2 to 2:1.
[0011] Furthermore, in the step (1), the mass ratio of the total mass of the metal source to boric acid is 1:5 to 2:1, preferably 1:2 to 2:1, the mass ratio of the total mass of the metal source to urea is 1:120 to 1:30, preferably 1:100 to 1:50, and the mass ratio of the total mass of the metal source to polyethylene glycol-2000 is 1:4 to 2:1, preferably 1:3 to 1:1.
[0012] Furthermore, in the step (1), the evaporation temperature is 60 to 100°C.
[0013] Furthermore, in step (2), the first heat treatment atmosphere is nitrogen or argon; the first heat treatment temperature is 750-1000°C, preferably 800-900°C; the heating rate is 2-10°C / min; the first heat treatment time is 1-5h, preferably 3-5h.
[0014] Furthermore, in the step (2), the acid etching uses 1-3 mol / L sulfuric acid, the acid etching temperature is 50-90° C., and the acid etching time is 3-12 h.
[0015] Furthermore, in step (2), the second heat treatment atmosphere is nitrogen or argon; the second heat treatment temperature is 750-1000°C, preferably 800-900°C; the heating rate is 2-10°C / min, and the heat treatment time is 1-5h, preferably 1-3h.
[0016] The present invention also provides a boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared by the above method, wherein the catalyst mainly comprises B, N, C, Co, and Ni, wherein Co and Ni are dispersed in single atoms and the average distance between atoms is 0.36 nm, the coordination structures of Co and Ni are CoN5 and NiN3B2 respectively, the Co atom loading is 0.5%, and the Ni atom loading is 1.5%. The matrix B and N co-doped carbon is in a nanotube shape with a tube diameter of about 50 to 150 nm, containing a mesoporous and macroporous multi-level pore structure, and the catalyst specific surface area is 470 to 650 m 2 / g, and the average pore size is 8-17nm.
[0017] The present invention also provides the application of the boron nitrogen carbon-based cobalt nickel double single-atom electrocatalyst in the preparation of synthesis gas by CO2 reduction, using carbon paper loaded with the boron nitrogen carbon-based cobalt nickel double single-atom electrocatalyst as a working electrode, a saturated silver / silver chloride electrode (or mercury / mercuric oxide electrode) as a reference electrode, a platinum sheet as a counter electrode, and a 0.5 mol / L potassium bicarbonate solution (or 1 mol / L potassium hydroxide solution) as an electrolyte, and an electro-reduction reaction of CO2 is carried out through a three-electrode system. Co in the catalyst exhibits excellent catalytic performance, and can keep the H2 / CO ratio stable at 1.5 in a wide potential range of -0.47 to -0.87 Vvs. RHE, and by adjusting the Co / Ni molar ratio in the precursor, the H2 / CO ratio can be controlled and adjusted between 0.5 and 3. In addition, the electrocatalyst also has excellent catalytic stability.
[0018] The beneficial effects of the present invention are as follows: 1. The boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared by the method described in the present invention has low-priced and readily available catalytic raw materials, a simple, economical, safe and reproducible preparation process, is easy to mass-produce, and has good prospects for industrial application. 2. The boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared by the method described in the present invention can obtain catalytic materials with different specific surface areas, different pore structures, different numbers and compositions of active sites by adjusting the raw material composition, heat treatment conditions and acid etching conditions, which is beneficial to improving catalyst performance and regulating the H2 / CO ratio. 3. In the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared by the method described in the present invention, the Co single atom is the main active site for producing H2, the Ni single atom is the main active site for producing CO, and the interaction between Co and Ni atoms is beneficial to the efficient and highly stable generation of synthesis gas. In the H-type electrolytic cell, the catalyst can maintain a stable H2 / CO ratio of 1.5 in a wide potential range of -0.47 to -0.87 V vs. RHE, and by adjusting the Co / Ni molar ratio in the precursor, the H2 / CO ratio can be controlled to be adjusted between 0.5 and 3. In the gas diffusion electrolytic cell, the current density is significantly increased, reaching as high as 1.0 V vs. RHE. 600mA · m -2 , and can be The H2 / CO ratio remains basically unchanged in a wide voltage range of -0.3 to -0.5 V vs. RHE. In addition, the electrocatalyst also has excellent catalytic stability, and the catalytic performance remains basically unchanged during the electrolysis process of up to 20 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Scanning electron microscope image of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention.
[0020] Figure 2 Transmission electron microscopy image of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention.
[0021] Figure 3 Spherical aberration corrected transmission electron microscopy image of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention.
[0022] Figure 4 Element distribution diagram of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention.
[0023] Figure 5 X-ray diffraction pattern of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention.
[0024] Figure 6 Raman spectrum of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention.
[0025] Figure 7 Nitrogen adsorption-desorption isotherm of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention.
[0026] Figure 8 Pore size distribution diagram of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention.
[0027] Fig. 9 X-ray photoelectron spectrum of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention.
[0028] Fig.10 Linear sweep voltammetry curve of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention in an H-type electrolytic cell.
[0029] Fig.11 CO Faraday efficiency, H2 Faraday efficiency, and hydrogen-carbon ratio of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention in an H-type electrolytic cell.
[0030] Fig.12 Linear sweep voltammetry curve of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention in a gas diffusion electrolytic cell.
[0031] Fig.13 CO Faraday efficiency, H2 Faraday efficiency, and hydrogen-carbon ratio of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 1 of the present invention in a gas diffusion electrolysis cell.
[0032] Fig.14 Linear sweep voltammogram of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 2 of the present invention in an H-type electrolytic cell.
[0033] Fig.15 CO Faraday efficiency, H2 Faraday efficiency, and hydrogen-carbon ratio of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 2 of the present invention in an H-type electrolytic cell.
[0034] Fig.16 Linear sweep voltammogram of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 3 of the present invention in an H-type electrolytic cell.
[0035] Fig.17 CO Faraday efficiency, H2 Faraday efficiency, and hydrogen-carbon ratio of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst prepared in Example 3 of the present invention in an H-type electrolytic cell. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but the embodiments of the present invention are not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] The preparation method of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst used for electrocatalytic CO2 reduction to produce synthesis gas in this embodiment is as follows:
[0039] (1) Weigh a certain amount of cobalt chloride, nickel chloride, boric acid, urea, and polyethylene glycol-2000 in a beaker, wherein the mass ratio of metal source cobalt chloride to nickel chloride is 1:1, the mass ratio of the total mass of the metal source to boric acid is 2:3, the mass ratio of the total mass of the metal source to urea is 1:55, and the mass ratio of the total mass of the metal source to polyethylene glycol-2000 is 1:5. Add 50 mL of deionized water, stir for 12 h, dry at 80 ° C in an oil bath, and grind to obtain a catalyst precursor.
[0040] (2) The prepared catalyst precursor was placed in a tubular furnace and heated to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere and maintained for 4 hours. After the heat treatment, the sample was placed in a 2 mol / L sulfuric acid solution, etched at 80°C for 4 hours, and then heated to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for a second heat treatment of 1 hour to obtain the final product, a boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst.
[0041] The surface area of the catalyst prepared in this example is 520.7 m 2 / g, the average pore size is 12.9nm. The loading amount of Co is 0.45%, and the loading amount of Ni is 1.49%.
[0042] 5 mg of the catalyst prepared in this example was weighed, 5 wt% Nafion solution (25 μL) and ethanol (475 μL) were added, and ultrasonicated for 60 min in an ultrasonic cleaner to form a uniform catalyst ink. Then, 100 μL of the catalyst ink was dropped on a 1×1 cm 2 On carbon paper, the catalyst loading after drying was 1 mg / cm 2The working electrode is a standard three-electrode system, with a silver / silver chloride electrode (or (or mercury / mercuric oxide electrode) as the reference electrode, a platinum electrode as the counter electrode, and a 0.5M CO2-saturated KHCO3 solution (or 1 mol / L potassium hydroxide solution) as the electrolyte, and electrolysis is carried out in an H-type electrolytic cell (or a gas diffusion electrolytic cell). The product is analyzed by gas chromatography equipped with a thermal conductivity detector (TCD) and a hydrogen flame ionization detector (FID) to analyze the content of CO and H2 in the product, and then the Faraday efficiency and H2 / CO ratio are calculated.
[0043] The characterization results of scanning electron microscopy, transmission electron microscopy, spherical aberration corrected transmission electron microscopy and element distribution diagrams show that the catalyst prepared in this example presents a one-dimensional nanotube structure, the metal on the catalyst is obviously dispersed in single atoms, and the Co, Ni, B, N, and C elements are evenly distributed on the carbon carrier, and no obvious metal agglomeration phenomenon is observed. Figure 1 , Figure 2 , Figure 3 and Figure 4 The XRD characterization results show that the catalyst prepared in this example mainly presents carbon diffraction peaks, and no obvious metal diffraction peaks, which indirectly indicates that the metal in the catalyst is dispersed in single atoms, such as Figure 5 The Raman spectroscopy results show that the catalyst prepared in this example has abundant defect sites, such as Figure 6 The N2 adsorption-desorption isotherm characterization results show that the catalyst prepared in this example has both mesopores and macropores. Figure 7 and Figure 8 The XPS total spectrum results show that the catalyst prepared in this example has Co, Ni, B, N, and C elements, such as Fig. 9 The electrochemical measurement results of the H-type electrolytic cell show that the catalyst prepared in this example exhibits excellent performance in the electroreduction of CO2 and H2O to produce synthesis gas. In a wide reduction voltage range (-0.47 to -0.87 V vs. RHE), the synthesis gas H2 / CO ratio remains stable at 1.5, and when the voltage is -0.87 V vs. RHE, the current density can reach as high as -38.8 mA cm -2 ,like Fig.10 and Fig.11 The catalyst prepared in this example was applied to a gas diffusion electrolytic cell, and the current density was significantly increased. When the voltage was -0.87 V vs. RHE, the current density could be increased to -496 mA·cm -2 , and in a wide reduction voltage range (-0.3 ~ -0.5V vs. RHE), the synthesis gas H2 / CO ratio remains stable at 0.6. Fig.12 and Fig.13 As shown, it can better meet the needs of industrial applications.
[0044] Example 2
[0045] According to the preparation method of Example 1, the mass ratio of cobalt chloride to nickel chloride in step (1) was adjusted to 1:2, and the other steps remained unchanged. The electrochemical performance measurement results of the H-type electrolytic cell showed that within a wide reduction voltage range (-0.57 to -0.97 V vs. RHE), the syngas H2 / CO ratio was close to 0.5, and when the voltage was -0.87 V vs. RHE, the current density could be as high as -50.6 mA cm -2 ,like Fig.14 and Fig.15 shown.
[0046] Example 3
[0047] According to the preparation method of Example 1, the molar ratio of cobalt chloride to nickel chloride in step (1) was adjusted to 2:1, and the other steps remained unchanged. The electrochemical performance measurement results of the H-type electrolytic cell showed that within a wide reduction voltage range (-0.67 to -0.97 V vs. RHE), the syngas H2 / CO ratio was close to 2, and when the voltage was -0.87 V vs. RHE, the current density was -23.7 mA cm -2 ,like Fig.16 and Fig.17 shown.
[0048] Example 4
[0049] According to the preparation method of Example 1, the first and second heat treatment temperatures in step (1) were adjusted to 900°C, and the other steps remained unchanged. The electrochemical performance measurement results of the H-type electrolytic cell showed that within a wide reduction voltage range (-0.67 to -0.87 V vs. RHE), the syngas H2 / CO ratio was close to 0.4, and when the voltage was -0.87 V vs. RHE, the current density was as high as -30.8 mA cm -2 .
[0050] In summary, the above embodiments are only for explaining the relevant principles and implementation methods, and are intended to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and are not intended to limit the present invention. Any modification, equivalent replacement, improvement, etc. made to the present invention without departing from the principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst, characterized in that: The electrocatalyst has a one-dimensional nanotube morphology with a tube diameter of 50 to 150 nm and a specific surface area of 470 to 650 m 2 / g, with an average pore size of 8 to 17 nm, including B, N, C, Co and Ni, wherein the matrix is B and N co-doped carbon with a nanotube morphology, Co and Ni are monoatomic dispersions, the Co atom loading is 0.5%, and the Ni atom loading is 1.5%.
2. The boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst according to claim 1, characterized in that: The electrocatalyst with nanotube morphology contains abundant mesoporous-macroporous multi-level pore structure, Co and Ni are dispersed in single atoms with an average distance between atoms of 0.36 nm, and the coordination structures of Co and Ni are CoN5 and NiN3B2 respectively.
3. The method for preparing the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst according to claim 1, characterized in that: The method is prepared by using cobalt chloride and nickel chloride as metal sources, boric acid as a boron source, polyethylene glycol-2000 as a first carbon source, urea as a nitrogen source and a second carbon source, and adopting a high-temperature pyrolysis and acid etching method.
4. The method for preparing the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst according to claim 3, characterized in that The method comprises the following preparation steps: (1) Weigh cobalt chloride, nickel chloride, boric acid, urea, and polyethylene glycol-2000 into a beaker, add deionized water, stir, and evaporate to dryness to obtain a catalyst precursor; (2) placing the catalyst precursor obtained in step (1) in a tubular furnace, and obtaining a boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst after a first heat treatment, etching in an acid solution, and a second heat treatment.
5. The method for preparing the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst according to claim 4, characterized in that: In the step (1), the mass ratio of cobalt chloride to nickel chloride is 1:5-5:1, the mass ratio of the total mass of metal source cobalt chloride and nickel chloride to boric acid is 1:5-2:1, the mass ratio of the total mass of metal source cobalt chloride and nickel chloride to urea is 1:120-1:30, the mass ratio of the total mass of metal source cobalt chloride and nickel chloride to polyethylene glycol-2000 is 1:4-2:1, and the stirring time in step (1) is 10-12h.
6. The method for preparing the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst according to claim 4, characterized in that: In the step (2), the first heat treatment atmosphere is nitrogen or argon, the first heat treatment temperature is 750-1000° C., the heating rate is 2-10° C. / min, and the first heat treatment time is 1-5 h.
7. The method for preparing the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst according to claim 4, characterized in that: In the step (2), the acid etching uses 1-3 mol / L sulfuric acid, the acid etching temperature is 50-90° C., and the acid etching time is 3-12 h.
8. The method for preparing the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst according to claim 4, characterized in that: In the step (2), the second heat treatment atmosphere is nitrogen or argon, the second heat treatment temperature is 750-1000° C., the heating rate is 2-10° C. / min, and the heat treatment time is 1-5 hours.
9. The use of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst according to claim 1 or 2 in the electroreduction of CO2 to produce synthesis gas, characterized in that: The carbon paper loaded with the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst is used as the working electrode, the saturated silver / silver chloride electrode or the mercury / mercury oxide electrode is used as the reference electrode, the platinum sheet is used as the counter electrode, and the 0.5 mol / L potassium bicarbonate solution or the 1 mol / L potassium hydroxide solution is used as the electrolyte. The electrocatalytic CO2 reduction reaction in the aqueous solution is carried out through a three-electrode system. The Co single atom is the main active site for H2 production, and the Ni single atom is the main active site for CO production. The interaction between Co and Ni atoms is conducive to the efficient and stable generation of synthesis gas with a suitable H2 / CO ratio in a wide voltage range.
10. The use of the boron-nitrogen-carbon-based cobalt-nickel double single-atom electrocatalyst according to claim 9 in the electroreduction of CO2 to produce synthesis gas, characterized in that: The H2 / CO ratio remains stable at 1.5 within a wide potential range of -0.47 to -0.87 V vs. RHE, and by adjusting the Co / Ni molar ratio in the precursor, the H2 / CO ratio can be controllably adjusted between 0.5 and 3, while exhibiting excellent catalytic stability.
